Thermoelectric properties of poly (3,4-ethylenedioxy thiophene)/poly (sulfonic acid diphenyl aniline) composites synthesized in the absence and presence of magnetic field - Ugraskan, Volkan; Karaman, Ferdane (IOP Publishing Ltd, 2020)
Poly(3,4-ethylenedioxy thiophene)/polysulfonic diphenyl aniline (PEDOT:PSDA) composites in the ratios of 1:0.5, 1:1, 1:1.5 and 1:2 were synthesized by oxidative chemical polymerization in the absence and presence of external constant magnetic field which the flux density is 3 kGa. The samples were characterized by UV-vis, FTIR-ATR and XRD. Their thermoelectric properties were obtained by means of electrical conductivities and Seebeck coefficients measurements. It was found that both the conductivity and Seebeck coefficients of the PEDOT:PSDA composites were increased in the presence of magnetic field. The conductivities of PEDOT:PSDA composites are lower whereas their Seebeck coefficients are considerably higher than that of commercial PEDOT:PSS. The highest power factor was obtained as 32 mu W m(-1)K(-2) for the composite PEDOTPSDA = 1:1 synthesized in the presence of magnetic field. The power factor of this sample was enhanced to 185 mu W m(-1)K(-2) by a secondary doping with sodium dodecyl benzene sulfonate.
Keywords: PEDOT; PSDA; composite; magnetic field; PEDOT-PSS; CONDUCTIVE POLYMERS; ENHANCEMENT; FILMS; POLYMERIZATION; PERFORMANCE; Materials Science